How gamma and electron-beam irradiations modulate phenolic profile expression in Melissa officinalis L. and Melittis melissophyllum L. - Pereira, Eliana (2018)
Owing to the overall increase in herbal infusions’ consumption, there's a progressively higher need of suitable plant material, as well as adequate conservation techniques to maintain its quality. Among, the available technologies, irradiation is gaining interest as a feasible preservation method. In line with this approach, this wok was designed to evaluate the effects of electron-beam and gamma irradiation over the phenolic profiles of two plant species Melissa officinalis L. (LB) and Melittis melissophyllum L. (BB). Individual phenolics were characterized by high-performance liquid chromatography coupled to a diode array detector and a mass spectrometer (HPLC-DAD-ESI/MS). Irradiated samples showed a general increase in individual phenolic contents, especially in lithospermic acid A in LB and 5-O-caffeoylquinic acid in BB. Thus, this study revealed the potential usefulness of both conservation technologies when employed to this type of plants.